Peran Masyarakat dalam Membentuk Akhlak Mahmudah dan Karakter Sosial Anak Sekolah Dasar - Anjani, Naela; Hamidah, Lailatul; Qolbi A., Nasywa Fairuzah; Firdausy, Nazwa Khilmi; Musthofa, M. Bahri (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2024)
This research aims to determine the role of the community in forming easy morals and the social character of children who attend elementary school  Jemurwonosari 1. This study looks at how community leaders and community efforts are involved in forming easy morals and supporting and inhibiting factors. This descriptive qualitative research uses data collection techniques through interviews and field observations. The problem studied is the role of society in shaping the easy morals and social character of elementary school children from the supporting and inhibiting factors of community activities in forming the easy morals and social character of children in the Jemurwonosari sub-district. This research shows how the local community participates in monitoring children’s behaviour and social character. The form of supervision is in the form of instaling CCTV in several hauses in the surrounding complex, holding regular, studies every weekend which aims to increase knowledge about religion by bringing in ulama figures from outside and collaborating with the school, especially the homeroom teacher so that they can monitor children’s activites while at school. the focus of this research emphasises that society as participants supports the formation of children’s Morals and social character.